Initial Design and Testing of Multiplayer Cooperative Game to Support Physical Activity in Schools - Oyelere, Solomon Sunday; Berghem, Simon Malmström; Brännström, Robert; Rutberg, Stina; Laine, Teemu; Lindqvist, Anna Karin (Education Sciences, 2022)
Recent studies have shown that children are not adequately physically active and there is a need to increase children’s physical activity. This study describes new opportunities and solutions for using existing games and gamification to increase physical activity among children in Sweden. We adopted the principles of Tic-Tac-Training to redesign, build, and test a classical multiplayer cooperative game, Battleship, to create a PA game that children experience as fun and engaging. The low fidelity prototype of the game was developed using an iterative game development life cycle and tested with 13 young male children aged 8–11 in a real-world informal setting. A mixed-method research approach was used to understand the users’ experiences and the impact of the Battleship-PA game on behavior change regarding physical activity. Research data were collected through audio recordings of interactions, direct observation, and a user experience questionnaire. The results of this study indicate both positive and negative feedback that can be used to improve the game and user experiences. The results from the unfiltered recordings revealed that both teams were competitive, cooperated within their team, and became excited whenever they destroyed opponent’s ships or were close to winning. However, the children felt bored and exhausted when many gamification tasks were repeated several times in a game session. Direct observation indicated that the children enjoyed the physical activities resulting from playing the game. However, participants who had not previously played the classical version of Battleship were confused about the objectives and concept of the game. The analysis of the user experience questionnaire indicated that most children found the game easy to play, motivating, engaging, interactive, fun, cooperative, competitive, and visually appealing. Furthermore, most children agreed that the game helped them to be physically active and strongly agreed that they enjoyed performing the physical activities in the game. Future work is needed to improve the game user interface, gamification elements, and prepare additional physical activity tasks for a rewarding experience.
Keywords: Active school transport; Formative evaluation; Game architecture; Gamification; Multiplayer cooperative game; Physical activity